Christology of the Old Testament: And a Commentary on the Messianic Predictions. Vol. 2 - Hengstenberg, Ernst Wilhelm, 1802-1869; Meyer, Theodore (Salt Lake City, UT : Project Gutenberg, 2009)
"Christology of the Old Testament: And a Commentary on the Messianic" by E. W. Hengstenberg is a theological study written in the mid-19th century. This work delves into the messianic prophecies found in the Old Testament, focusing particularly on the prophetic figure of Isaiah and his portrayal of Christ. Hengstenberg$1 (Bs analysis seeks to demonstrate the roots of Christological understanding within the Old Testament scriptures, highlighting how these ancient texts foreshadow the coming of the Messiah. The opening of this work provides a thorough introduction to Isaiah as a pivotal prophetic voice during the Assyrian period. Hengstenberg discusses the significance of Isaiah's prophecies, framing them as not only warnings but also as indications of hope and salvation through the coming Messiah. The text emphasizes the need for a moral transformation of the people of Israel before they can fully realize God's promises. As such, the early chapters lay the groundwork for understanding the relationship between the prophetic declarations and the overarching theme of divine redemption within the Old Testament's narrative. (This is an automatically generated summary.)s
Release date is 2009-12-05
Produced by Charles Bowen, from images obtained from Google Books.
Keywords: Messiah -- Prophecies; Bible. Old Testament -- Prophecies